Current Biochemical Applications and Future Prospects of Chlorotoxin in Cancer Diagnostics and Therapeutics - Sbonelo Khanyile; Priscilla Masamba; Babatunji Emmanuel Oyinloye; Londiwe Simphiwe Mbatha; Abidemi Paul Kappo (Tabriz University of Medical Sciences, 2019)
Chlorotoxin (CTX) is a minute 4 kDa protein made up of 36 amino acid residues, commonly known for its binding affinity to chloride channels and matrix metalloproteinase-2 (MMP-2) of glioma tumors of the spine and brain. This property and the possibility of conjugating this peptide to nanoparticles have enabled its diverse use in various biotechnological and biomedical applications for cancer treatment, such as in tumor imaging and radiotherapy. Because of the fascinating biological properties CTX possesses, elucidating its mechanism of action may hold promise for the development of new and effective therapeutic drugs, as well as more sensitive and highly specific cancer-screening kits. This article therefore reviews the currently known applications of CTX and suggests diverse ways in which it can be applied for the design of improved drugs and diagnostic tools for cancer.